Áp dụng mô hình phương trình cấu trúc bình phương bé nhất từng phần (PLS-SEM) cho nghiên cứu về lòng tin và hạnh phúc của cư dân đô thị tại Thành phố Hồ Chí Minh - Nguyễn Lê Hoàng Thụy Tố , Quyên; Phạm Quang Anh, Thư (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study aims to understand the role of trust in the happiness model of urban residents. The PLS-SEM technique was used to analyze a dataset of 300 households in Ho Chi Minh City, Vietnam, applying a stratified sampling strategy. The research results show that particular trust has a strong and statistically significant impact on happiness across all three aspects such as: individual, family and environment. In addition, the study provides evidence of a statistically significant impact of generalized trust on happiness in the environmental and family aspects. Meanwhile, institutional trust contributes to promoting individual happiness. Multi-group analysis reveals significant differences of trust on happiness categorized by age, gender and education. The findings highlight the practical importance of different dimensions of trust in enhancing specific domains of happiness among diverse groups of urban residents. This is the scientific basis for proposing focused policy implications for urban residents to achieve optimal happiness.